Attitude towards use of ICT and its actual level of use in English language teaching in Miri, Sarawak / Elina Faradilla Nurul Huda @ Ariffin - Nurul Huda @ Ariffin, Elina Faradilla (2010)
This survey investigated whether a sample of 60 English teachers from eight primary schools in Miri, Sarawak have a satisfactory attitude towards the use of ICT in teaching English and whether their actual level of classroom ICT use is satisfactory. The score would be considered satisfactory if the sample mean exceeds the median value. Both attitude level and actual ICT use level were found to be satisfactory as both scores marginally exceeded the median value, implying that frequent workshops can raise attitude level and actual use level even further. The population is the primary school English teachers in Miri. The three-section questionnaire was found to be reliable, (alpha = 0.86). Investigations indicated that attitude towards ICT correlated positively with the level of its use, (r = 0.638, p < 0.05), implying that the attitude level has to be raised if ICT use in the classroom is to be enhanced. However the age correlated inversely with the attitude score (r = -0.614, p < 0.05), indicating that the older teachers have problems adapting to ICT and need more training. Also investigated was the existence of any significant difference in attitude towards ICT use between the younger and the older teachers and between those who have attended ICT workshops and those who have not. There was a significant difference in attitude between the younger and the older teachers and also between those who have attended ICT workshops and those who have not. This shows that there should be more workshops involving a bigger number of teachers. Training sessions should also be customized to meet the needs of the older teachers.